Optimal scheduling of solar-surface water source heat pump system based on an improved arithmetic optimization algorithm - Qiu, Yirong; Wu, Lianghong; Zuo, Cili; Jia, Rui; Zhang, Hongqiang (Egyptian informatics journal, 2023)
Integrating solar energy into the combined energy supply of surface water source heat pump systems is expected to reduce the electricity consumption and carbon emissions. In this paper, a solar-surface water source heat pump system model is established to maximize system performance and save economic cost. In order to find the optimal operation scheme, an improved arithmetic optimization algorithm (iAOA) is proposed. This algorithm integrates elite opposition-based and nonlinear acceleration functions to solve the model. The effectiveness of the proposed model and algorithm is verified by applying it to a SWSHP district energy system in the central area of Xiangtan city. Experimental results demonstrate that incorporating solar energy into the SWSHP district energy system can improve system performance and reduce operational costs. In comparison with several other optimization algorithms, this algorithm has a faster convergence speed and a higher convergence accuracy. Therefore, it is considered an effective method for solving solar-surface water source heat pump district energy systems.